2023
DOI: 10.3390/pharmaceutics15020619
|View full text |Cite
|
Sign up to set email alerts
|

HS 3D-SeboSkin Model Enables the Preclinical Exploration of Therapeutic Candidates for Hidradenitis Suppurativa/Acne Inversa

Abstract: Despite the rapid development in hidradenitis suppurativa (HS) research, the immediate introduction of potent therapeutic compounds in clinical trials and the lack of definitive outcome measures have led to the discontinuation of potential therapeutic compound studies. HS is a solely human disease, and therefore, the search for preclinical human models has been given priority. The 3D-SeboSkin model, a co-culture of human skin explants with human SZ95 sebocytes as a feeder layer, has been shown to prevent the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Similar features, albeit to a lesser extent, were observed with co‐culture with fibroblasts. These results confirm findings of previous studies that showed preservation of skin integrity in the 3D‐SeboSkin model 20,22,23 . Interestingly, basal keratinocytes of co‐cultured skin explants proliferated and migrated to cover the exposed dermal surface in the 3D‐SeboSkin and to a lesser extent in co‐culture with fibroblasts, whereas in SFM this phenomenon was absent.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Similar features, albeit to a lesser extent, were observed with co‐culture with fibroblasts. These results confirm findings of previous studies that showed preservation of skin integrity in the 3D‐SeboSkin model 20,22,23 . Interestingly, basal keratinocytes of co‐cultured skin explants proliferated and migrated to cover the exposed dermal surface in the 3D‐SeboSkin and to a lesser extent in co‐culture with fibroblasts, whereas in SFM this phenomenon was absent.…”
Section: Resultssupporting
confidence: 91%
“…These results confirm findings of previous studies that showed preservation of skin integrity in the 3D-SeboSkin model. 20,22,23 Interestingly, basal keratinocytes of cocultured skin explants proliferated and migrated to cover the exposed dermal surface in the 3D-SeboSkin and to a lesser extent in co-culture with fibroblasts, whereas in SFM this phenomenon was absent. Furthermore, the dermis in all models showed variable degrees of features of coagulative cell death in the form of paleness, decreased vasculature and fragmentation of the collagen fibres but without inflammatory infiltrate due to absence of the blood circulation 27,28 (Figures S2 and S3).…”
Section: Structural Epidermal Integrity Of Skin Explants Is Maintaine...mentioning
confidence: 98%
See 3 more Smart Citations